PEMANFAATAN SAMPAH SAYURAN RUMAH TANGGA MENJADI PELET PAKAN IKAN LELE (CLARIAS GARIEPINUS) - Dimas Putra Pratama; Iva Rustanti Eri W; Ngadino (Gema Lingkungan Kesehatan, 2022)
Vegetable waste that is not utilized causes an unpleasant odor effect and disturbs the aesthetics of the environment, wet waste thrown away can become a breeding ground for insects. One of the waste utilization methods is the manufacture of fish pellets. The purpose of this study is to utilize household vegetable waste used for fish feed pellets. The research design used was a pre-experimental design with a posttest only research design. The object of this research is vegetable waste originating from household activities. The treatments used were 3 variations of vegetables (20%, 30%, 40%) repetition which was carried out 3 times with a concentration of 1 kg. Making fish pellets using a machine that has been modified as a supporting tool for making pellets. The pellets produced were subjected to laboratory tests to determine the water content, ash content, fat content, crude fiber content, protein content referring to SNI (01-4087-2006) concerning catfish feed regulations. The results showed that from variation 1 (20%), variation 2 (30%) and variation 3 (40%) none of them met the Indonesian National Standard with water content, ash content, fat content, and protein content. crude fiber still does not meet because it is still under the provisions of SNI. It was concluded that there were no pellets made from vegetable waste that met the stipulation value of SNI. The percentage that can be reviewed for the formulation is that the percentage of shrimp head flour can be increased to 20% and the fine bran can be reduced to 40%. For the community, it can be useful to overcome the problem of vegetable waste being dumped directly into the surrounding environment without any processing of the vegetable waste to be used as fish feed pellets.